2016
DOI: 10.1186/s13047-016-0171-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic examination of plantar fasciitis: a comparison of patient positions during examination

Abstract: BackgroundMusculoskeletal ultrasound is a non-invasive and low-cost modality for real-time visualisation of the plantar fascia. Ultrasound examination for plantar fasciitis is generally performed with the patient in a prone position, although the rational for using a prone position has not been validated. The aim of the study was to investigate if ultrasound examination in a supine position, which is more comfortable than the prone position, is valid.MethodsWe conducted a prospective study of 30 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…MRI is the imaging modality of choice in confirming the diagnosis of plantar fasciitis. However, ultrasonography has the advantages of easy accessibility, lower cost, it is relatively fast, and has very good spatial resolution for superficial structures; hence, it is used increasingly in the diagnosis of plantar fasciitis [ 23 , 24 ]. There are few studies on the role of ultrasound elastography, which can detect initial changes in plantar fascia stiffness before the detection of findings on routine ultrasound [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the imaging modality of choice in confirming the diagnosis of plantar fasciitis. However, ultrasonography has the advantages of easy accessibility, lower cost, it is relatively fast, and has very good spatial resolution for superficial structures; hence, it is used increasingly in the diagnosis of plantar fasciitis [ 23 , 24 ]. There are few studies on the role of ultrasound elastography, which can detect initial changes in plantar fascia stiffness before the detection of findings on routine ultrasound [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge and as evoked in the Introduction, this study is the first of its kind. The pertinence of such study resides in the fact that (i) oral DK has shown better analgesic and anti-inflammatory effects compared to DS when they were administered orally; (ii) DS exists in (spray) gels (and patches) for topical application [ 29 ] and is commercialized, whereas we failed to find studies related to marketed DK gels; (iii) phonophoresis is commonly used in combination with DS gels for the treatment of musculoskeletal injuries [ 38 , 39 ], and it was proved more effective than DS alone [ 39 , 40 ], but no studies have evaluated phonophoresis in combination with diclofenac derivatives, such as DK.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, medication particles are pushed deep into the skin tissue by ultrasound waves. A resting membrane potential caused by DK relaxed muscles and phonophoresis increases the penetration of the drug into tissues and circulation, which in turn decreased pain and inflammation [ 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of the vertical thickness of the plantar fascia were made from the anterior aspect of the inferior border of the calcaneus (figure 2). 7 The built-in ultrasound caliper tool was used to make the measurements. The plantar fascia was measured at the initial visit, the final visit, and at the cross-over visit for subjects in the control group.…”
Section: Pi = Principle Investigatormentioning
confidence: 99%